2019 Russell Ross Memorial Lecture in Vascular Biology: B Lymphocyte–Mediated Protective Immunity in Atherosclerosis. Issue 2 (February 2020) - Upadhye, Aditi; Sturek, Jeffrey M.; McNamara, Coleen A.
Abstract : Atherosclerosis—the major underlying pathology of cardiovascular disease—is characterized by accumulation and subsequent oxidative modification of lipoproteins within the artery wall, leading to inflammatory cell infiltration and lesion formation that can over time result in arterial stenosis, ischemia, and downstream adverse events. The contribution of innate and adaptive immunity to atherosclerosis development is well established, and B cells have emerged as important modulators of both pro- and anti-inflammatory effects in atherosclerosis. Murine B cells can broadly be divided into 2 subsets: (1) B-2 cells, which are bone marrow derived and include conventional follicular and marginal zone B cells, and (2) B-1 cells, which are largely fetal liver derived and persist in adults through self-renewal. B-cell subsets are developmentally, functionally, and phenotypically distinct with unique subset-specific contributions to atherosclerosis development. Mechanisms whereby B cells regulate vascular inflammation and atherosclerosis will be discussed with a particular emphasis on B-1 cells. B-1 cells have a protective role in atherosclerosis that is mediated in large part by IgM antibody production. Accumulating evidence over the last several years has pointed to a previously underappreciated heterogeneity in B-1 cell populations, which may have important implications for understanding atherosclerosis development and potential targeted therapeutic approaches. This heterogeneity within atheroprotective innate B-cell subsets will be highlighted.